The impact of different warm-up protocols on vertical jump performance in male collegiate athletes - Holt, B. W.; Lambourne, K. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to compare the impact of different types of warm-up on countermovement vertical jump (VJ) performance. Sixty-four male Division I collegiate football players completed a pretest for VJ height. The participants were then randomly assigned to a warm-up only condition, a warm-up plus static stretching condition, a warm-up plus dynamic stretching condition, or a warm-up plus dynamic flexibility condition. VJ performance was tested immediately after the completion of the warm-up. The results showed that there was a significant difference (P < .05) in VJ performance between the warm-up groups. Posttest jump performance improved in all groups; however, the mean for the static stretching group was significantly lower than the means for the other 3 groups. The static stretching negated the benefits gained from a general warm-up when performed immediately before a VJ test.